Luminescent Pb-free perovskites: low-cytotoxicity materials for primary thermal sensing - Passini, Luan N.; Maturi, Fernando E. [UNESP]; Pugina, Roberta S.; Hilário, Eloísa G.; Fontes, Marina; Barud, Hernane S.; Carlos, Luís D.; Caiut, José Maurício A.; Manzani, Danilo (Royal Society of Chemistry (RSC), 2023)
Selecting a suitable host matrix to perform temperature sensing in biomedical applications requires low cytotoxicity, facile synthesis, and an ability to be doped with light-emitting ions. With this perspective, indium-based halide double perovskites, specifically Cs2AgIn0.9Bi0.1Cl6, Cs2Ag0.6Na0.4InCl6, and Cs2Ag0.6Na0.4In0.9Bi0.1Cl6, were chosen as host materials to develop lanthanide-based primary thermometers due to their low phonon energy and ease of synthesis. The incorporation of Na+ and Bi3+ into the perovskite cubic crystal lattice was confirmed by X-ray diffraction and Raman spectroscopy while the optical properties of both the undoped and Yb3+/Er3+ co-doped perovskites were assessed by diffuse reflectance and photoluminescence spectroscopies. The obtained perovskite samples demonstrated excellent thermal stability, with the ability to withstand temperatures as high as 500 °C. A temperature-dependent green emission of Er3+ was observed in the co-doped samples upon 980 nm irradiation, yielding a relative thermal sensitivity and uncertainty in temperature values of 1.3% K−1 and 0.3 K, respectively. Incorporating the obtained perovskites (0.05 to 0.20 mg mL−1) into L2929 cells as an in vitro model resulted in high cell viability, underscoring the benefits of selecting such a low-cytotoxicity material for applications in biological media.